The Post-Soviet State Systems’ Resilience: An Outline of the Theoretical Model - V. V. Yakunin; I. I. Kuznetsov; M. V. Vilisov (Контуры глобальных трансформаций: политика, экономика, право, 2020)
An upcoming anniversary of the USSSR dissolution raises the opportunity to overview the tendencies of the  development of the state systems, emerged on its fragments. A retrospective view of this process, which has received various (sometimes contradictory) political and expert assessments, raises the main question – the viability and prospects of sustainable development of the former USSR countries.The shared past continues to have a significant impact through the Soviet legacy, making these countries difficult  to analyze and raise questions about the effectiveness of common tools for assessing their resilience and stability.The paper describes the application of the model of resilience and stability of the state systems, developed earlier in a co-authorship within the framework of joint research. The estimates obtained make it possible to form the  profile of some countries and determine the structural imbalances in the development of their state systems in terms of resilience and stability.